Enhanced production of natural yellow pigments from Monascus purpureus by liquid culture: The relationship between fermentation conditions and mycelial morphology - Lv, Jun; Zhang, Bo-Bo; Liu, Xiao-Dong; Zhang, Chan; Chen, Lei; Xu, Gan-Rong; Cheung, Peter Chi Keung (Journal of bioscience and bioengineering, 2017)
Natural yellow pigments produced by submerged fermentation of Monascus purpureus have potential economic value and application in the food industry. In the present study, the relationships among fermentation conditions (in terms of pH and shaking/agitation speed), mycelial morphology and the production of Monascus yellow pigments were investigated in both shake-flask and scale-up bioreactor experiments. In the shake-flask fermentation, the highest yield of the Monascus yellow pigments was obtained at pH 5.0 and a shaking speed of 180 rpm. Microscopic images revealed that these results were associated with the formation of freely dispersed small mycelial pellets with shorter, thicker and multi-branched hyphae. Further investigation indicated that the hyphal diameter was highly correlated with the biosynthesis of the Monascus yellow pigments. In a scaled-up fermentation experiment, the yield of yellow pigments (401 U) was obtained in a 200-L bioreactor, which is the highest yield to the best of our knowledge. The present findings can advance our knowledge on the conditions used for enhancing the production of Monascus yellow pigments in submerged fermentation and facilitate large-scale production of these natural pigments. •Control of pH and shaking speed in the production of natural Monascus yellow pigments.•Mycelial morphology of Monascus purpureus was greatly affected by culture conditions.•The hyphal diameter was correlated with the biosynthesis of Monascus yellow pigments.•Scale-up production of the Monascus yellow pigments was achieved at 401 U/mL.